Efecto de varios inoculos de leguminosas sobre soya y frijol - Prieto, H.=700 1 Agudelo, O.; Varela G, R.
(Es, En)
Ilus., 11 ref.
Keywords: LEGUMINOSAS; GLYCINE MAX; PHASEOLUS VULGARIS; INOCULACION; RHIZOBIUM; NODULACION; BACTERIA FIJADORA DEL NITROGENO; COLOMBIA; ACTA AGRONOMICA